2005
DOI: 10.1590/s0103-97332005000500036
|View full text |Cite
|
Sign up to set email alerts
|

A direct measurement of the neutron-neutron scattering length

Abstract: A direct measurement of nn-scattering by colliding free neutrons has never been performed. Indirect measurements continue to provide inconsistent results, leaving the issue of charge symmetry in the nuclear force unresolved. At present the Russian pulsed reactor YAGUAR is the best neutron source for such a measurement. A neutron moderator is installed in the central through channel and the scattered neutrons are detected at a distance of 12 m from the reactor. An instantaneous value of 1.1 × 10 18 /cm 2 s was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…From the chart of nuclides in [1], we observe that the most unstable nuclei are located at the extreme edge to the right as well as to the left of the valley of stability, that is, at the borders of the chart one finds nuclei with quite small half-life times, forming the wiggled delimiting lines; for this reason they do not actively participate of the ordinary matter constitution but contribute for the production, through decay processes, of nuclei that are stable or radioactive with non-null relative abundance. A nice exposition on nuclear 10 From the quantum mechanical scattering theory of colliding nucleons a negative scattering length is an indication of the non-existence of a bound state, and, experimentally, it is found that colliding protonproton and neutron-neutron show a negative scattering length, thus dineutron and diproton cannot have stable structures, see [27,28]. The proton-neutron system has a single bound state: the deuteron.…”
Section: Semi-empirical Nuclide Mass Formulamentioning
confidence: 99%
“…From the chart of nuclides in [1], we observe that the most unstable nuclei are located at the extreme edge to the right as well as to the left of the valley of stability, that is, at the borders of the chart one finds nuclei with quite small half-life times, forming the wiggled delimiting lines; for this reason they do not actively participate of the ordinary matter constitution but contribute for the production, through decay processes, of nuclei that are stable or radioactive with non-null relative abundance. A nice exposition on nuclear 10 From the quantum mechanical scattering theory of colliding nucleons a negative scattering length is an indication of the non-existence of a bound state, and, experimentally, it is found that colliding protonproton and neutron-neutron show a negative scattering length, thus dineutron and diproton cannot have stable structures, see [27,28]. The proton-neutron system has a single bound state: the deuteron.…”
Section: Semi-empirical Nuclide Mass Formulamentioning
confidence: 99%